Regional cerebral blood flow as predictor of response to occipital nerve block in cluster headache - Sonia Medina (The Journal of Headache and Pain, 2021)
Abstract Background Cluster headache is an excruciating disorder with no cure. Greater occipital nerve blockades can transiently suppress attacks in approximately 50% of patients, however, its mechanism of action remains uncertain, and there are no reliable predictors of treatment response. To address this, we investigated the effect of occipital nerve blockade on regional cerebral blood flow (rCBF), an index of brain activity, and differences between treatment responders and non-responders. Finally, we compared baseline perfusion maps from patients to a matched group of healthy controls. Methods 21 male, treatment-naive patients were recruited while in a cluster headache bout. During a pain-free phase between headaches, patients underwent pseudo-continuous arterial spin labelled MRI assessments to provide quantitative indices of rCBF. MRIs were performed prior to and 7-to-21 days following treatment. Patients also recorded the frequency of their headache attacks in a daily paper diary. Neuropsychological assessment including anxiety, depression and quality of life measures was performed in a first, scanning free session for each patient. Results Following treatment, patients demonstrated relative rCBF reductions in posterior temporal gyrus, cerebellum and caudate, and rCBF increases in occipital cortex. Responders demonstrated relative rCBF increases, compared to non-responders, in medial prefrontal cortex and lateral occipital cortex at baseline, but relative reductions in cingulate and middle temporal cortices. rCBF was increased in patients compared to healthy controls in cerebellum and hippocampus, but reduced in orbitofrontal cortex, insula and middle temporal gyrus. Conclusions We provide new mechanistic insights regarding the aetiology of cluster headache, the mechanisms of action of occipital nerve blockades and potential predictors of treatment response. Future investigation should determine whether observed effects are reproducible and extend to other headache disorders.